Comparative genomics analyses revealed two virulent Listeria monocytogenes strains isolated from ready-to-eat food - Lim, S.Y.; Yap, K.P.; Thong, Kwai Lin (BioMed Central, 2016)
Background: Listeria monocytogenes is an important foodborne pathogen that causes considerable morbidity in humans with high mortality rates. In this study, we have sequenced the genomes and performed comparative genomics analyses on two strains, LM115 and LM41, isolated from ready-to-eat food in Malaysia. Results: The genome size of LM115 and LM41 was 2,959,041 and 2,963,111 bp, respectively. These two strains shared approximately 90% homologous genes. Comparative genomics and phylogenomic analyses revealed that LM115 and LM41 were more closely related to the reference strains F2365 and EGD-e, respectively. Our virulence profiling indicated a total of 31 virulence genes shared by both analysed strains. These shared genes included those that encode for internalins and L. monocytogenes pathogenicity island 1 (LIPI-1). Both the Malaysian L. monocytogenes strains also harboured several genes associated with stress tolerance to counter the adverse conditions. Seven antibiotic and efflux pump related genes which may confer resistance against lincomycin, erythromycin, fosfomycin, quinolone, tetracycline, and penicillin, and macrolides were identified in the genomes of both strains. Conclusions: Whole genome sequencing and comparative genomics analyses revealed two virulent L. monocytogenes strains isolated from ready-to-eat foods in Malaysia. The identification of strains with pathogenic, persistent, and antibiotic resistant potentials from minimally processed food warrant close attention from both healthcare and food industry.